RANCANG BANGUN MESIN PENGADUK DAN PENCETAK ADONAN GETHUK PISANG UNTUK INDUSTRI SKALA RUMAHAN KAPASITAS 30 kg/JAM - Ahmad Syaifudin; Tri Andi Setiawan; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Gethuk pisang is a food product made from banana which is a traditional food from Kediri Regency. However, gethuk pisang production process still uses the traditional method. Of course that was require more time and labor to meet consumer demands. Machines to improve the gethuk pisang production process have been made before, but these machines are still not optimal in terms of production capacity. Therefore, we need an idea and innovation to create a machine to improve the production of gethuk pisang in the form of a machine for mixing and molding the dough of gethuk pisang for home-scale industries. The machine manufacturing process will use the Ulrich method from identifying machine requirements to selecting concepts and fabrication. Based on the results of the design using the Ulrich method, the design concept was chosen 1. Then planning, calculation and analysis will be carried out to determine the components to build the machine. The next stage is making of detailed drawings of the machine, followed by the fabrication and testing process. In testing the mixer and molding machine for gethuk pisang’s dough, the machine is capable of producing 31.74 kg per hour with a total cost of Rp.6,491,500,-.